Answer :

Put n = 1

a1 = 5 – 6(1) = 5 – 6 = -1


Put n = 2


a2= 5 – 6(2) = 5 – 12 = -7


a = -1, d = -7 + 1 = -6


Sn = [2a + (n – 1) d]


= [2(-1) + (n -1) (-6)]


= [-1 + 3n + 3]


= n [2 -3n]


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos
Arithmetic Progression- Don't miss these QuestionsArithmetic Progression- Don't miss these QuestionsArithmetic Progression- Don't miss these Questions56 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses